2015
DOI: 10.1038/nrc3893
|View full text |Cite
|
Sign up to set email alerts
|

S100 proteins in cancer

Abstract: In humans, the S100 protein family is composed of 21 members that exhibit a high degree of structural similarity, but are not functionally interchangeable. This family of proteins modulates cellular responses by functioning both as intracellular Ca2+ sensors and as extracellular factors. Dysregulated expression of multiple members of the S100 family is a common feature of human cancers, with each type of cancer showing a unique S100 protein profile or signature. Emerging in vivo evidence indicates that the bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
741
2
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 674 publications
(761 citation statements)
references
References 185 publications
(175 reference statements)
11
741
2
7
Order By: Relevance
“…17 , 18 High S100A4 levels in colorectal tumors are associated with aggressive growth, metastasis, poor prognosis, and shortened patient survival times. 33 However, its role in colon cancer progression remains to be adequately tested.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 , 18 High S100A4 levels in colorectal tumors are associated with aggressive growth, metastasis, poor prognosis, and shortened patient survival times. 33 However, its role in colon cancer progression remains to be adequately tested.…”
Section: Resultsmentioning
confidence: 99%
“…17 , 18 Previous studies have reported that S100A4 is expressed in a variety of cells, such as fibroblasts, macrophages, and malignant cells, and plays a crucial role in mediating tumor-stromal interplay. 19-23 S100A4 functions as both intracellular and extracellular forms.…”
Section: Introductionmentioning
confidence: 99%
“…La surexpression d'une dizaine de membres de la famille des protéines S100 a été mise en évidence dans différents types de cancers (côlon, prostate, poumons, sein, etc.) [5]. Cette surexpression est associée à des phénotypes incluant la croissance tumorale, l'angiogenèse, la métastase ou encore l'évasion immunitaire, par des mécanismes dépendant de RAGE [5,6].…”
Section: Liens D'intérêtunclassified
“…Cette surexpression est associée à des phénotypes incluant la croissance tumorale, l'angiogenèse, la métastase ou encore l'évasion immunitaire, par des mécanismes dépendant de RAGE [5,6]. RAGE et les protéines S100 sont par conséquent considérés comme des cibles prometteuses pour le développement de nouvelles thérapies anti-cancéreuses [5]. Toutefois, plusieurs études récentes ont montré un rôle potentiellement béné-fique des interactions RAGE:S100 dans certains contextes cellulaires [4].…”
Section: Liens D'intérêtunclassified
“…It is a main factor not only in the inflammatory response but also in breast, prostate, and thyroid cancers. Recently, S100A8 has been reported to be related to proliferation and metastasis of tumors (Bresnick et al, 2015). Research on the relation of S100A8 to leukemia has been actively studying, because it is known that S100A8 is regulated in the differentiation process of HL-60, a human Caucasian promyelocytic leukemia cell (Asakura et al, 2016;Yang et al, 2016).…”
Section: Main Text S100a8mentioning
confidence: 99%